3D optical/CT as a preclinical companion imaging platform for glioblastoma drug development - Andrei Molotkov; Mikhail Doubrovin; Nikunj Bhatt; Fang-Chi Hsu; Amanda Beserra; Rajiv Chopra; Akiva Mintz (Taylor & Francis Group, 2020)
Multimodality 3D Optical Imaging (OI)/CT has the potential to play a major role in drug development for glioblastomas (GBM), as it is an accessible preclinical method. To demonstrate the potential of 3D OI/CT to visualize orthotopic GBM implantation, we labeled GBM cells with Cy7 and imaged their location using 3D OI/CT. To confirm the accuracy of the spatial localization and demonstrate the ability to image locoregionally delivered therapies, we labeled mouse albumin with Cy7 (Cy7ALB) and delivered it via locoregional infusion 1 mm or 3 mm into the brain and demonstrated correlation of signal between the 3D OI/CT and post necropsy brain slices. In addition, we demonstrated the potential of systemically delivered Cy7ALB contrast to detect blood-brain barrier (BBB) permeability caused by orthotopic GBMs using 3D OI/CT. We also tested the potential of 3D OI/CT to assess focal BBB permeability induced by high intensity focused ultrasound (HIFU), a methodology being used in clinical trials to noninvasively permeabilize the BBB for systemic therapeutic delivery to GBM. We demonstrated the ability of systemic Cy7ALB contrast together with 3D OI/CT to accurately assess real-time HIFU-induced BBB permeability, which correlated to post necropsy imaging of brains. Furthermore, we demonstrated that 3D OI/CT can also image the therapeutic distribution of a Cy7-labeled anti-PD-1 antibody, a prototype translational antibody therapy. We successfully imaged real-time antibody distribution after HIFU-induced BBB permeability, which correlated with post necropsy Cy7 signal and translational PET imaging after injection of [89Zr] anti-PD-1 antibody. Thus, we demonstrated the broad potential of using 3D OI/CT as an accessible preclinical tool to develop anti-GBM therapies.